Determination of Three Capsaicinoids in Raw Red Pepers and Seasoning Powders by Liquid Chromatography with Coulometric Detection. Issue 6 (1st March 2017) - Watanabe, Hayaki; Murakami, Kazuo; Imazawa, Hiroka; Kauffmann, Jean‐Michel
Abstract: The simultaneous determination of three capsaicinoids in raw red pepper and in foods was studied by liquid chromatography coupled to a coulometric detector. The capsaicinoids were separated on an ODS C18 reversed column by isocratic elution with a mobile phase based on acetonitrile −0.15 M acetic acid (51:49%, v/v) at a flow rate of 0.8 mL min −1 . The limit of detection (S/N> 3) was 10 pg (injected mass) at an applied potential of 0.650 V vs. Pd. The peak area of the three studied compounds was found to be related to the amount injected from 50 pg to 100 ng range (r=0.999). The relative standard deviation (RSD, n=10) was comprised between 1.5∼4.4 and 1.0∼3.5 % for 100 pg and 5 ng, respectively. The determination of three capsaicinoids in raw red peppers and red pepper containing foods was successfully realized. Abstract :